The effect of Cinnamon Aromatherapy (Cinnamon Essential Oil) on Primary Dysmenorrhea in Adolescents. - Shielvia Franciska Sari; Ririn ` Indrian; Lumastari Ajeng Wijayanti; Eny Sendra (Jurnal Kebidanan Manna, 2026)
Introduction: Primary dysmenorrhea is menstrual pain without reproductive organ abnormalities experienced by most adolescent girls, with a prevalence reaching 45–95% globally and 60–70% in Indonesia. Untreated pain can limit physical activity and decrease the quality of life. This study aims to analyze the effect of cinnamon aromatherapy (Cinnamon Essential Oil) on reducing primary dysmenorrhea in adolescents. Methods: This study used a pre-experimental one-group pretest-posttest design. The population consisted of 56 third-year female students at the Health Polytechnic of the Ministry of Health Malang, Campus IV Kediri, with a sample of 36 respondents selected through a simple random sampling technique. Pain intensity was measured using the Numeric Rating Scale (NRS) observation sheet before and after the inhalation of cinnamon aromatherapy for 15–20 minutes. Data were analyzed using the Wilcoxon Signed-Rank test. Results: Before the intervention, nearly half of the respondents (47.2%) experienced moderate dysmenorrhea, 36.1% mild, and 16.7% severe, with no respondents being pain-free. After the administration of cinnamon aromatherapy, 30.6% of respondents no longer felt pain, 33.3% experienced mild and moderate pain respectively, while severe pain decreased to only 2.8%. The Wilcoxon test showed a p-value = 0.00$ with Z = -4.848, indicating a significant effect. This effect is attributed to the cinnamaldehyde and eugenol content, which possess antispasmodic and anti-inflammatory properties, thereby inhibiting prostaglandin synthesis and relaxing uterine muscles. Additionally, the aroma of cinnamon stimulates the release of serotonin and endorphins through the limbic olfactory pathway, inducing a relaxing effect and reducing pain perception. Conclusion: Cinnamon aromatherapy is proven effective in reducing the intensity of primary dysmenorrhea in adolescents. Suggestions: This intervention can be recommended as a safe, inexpensive, and easy-to-apply non-pharmacological therapy. Health education institutions are expected to utilize this intervention as a complementary alternative to reduce dependence on analgesic drugs in dysmenorrhea management.